A formação empreendedora de jovens brasileiros em vulnerabilidade socioeconômica: o caso de Minas Gerais - Henriqueta Morais Bernardes (2023)
Entrepreneurship is the ability of a person to identify problems and opportunities, develop solutions and invest resources in creating something positive for society, which generates real changes and impacts on people's daily lives, whether in the form of a business or a project. or even a movement. It is considered the art of making personal or organizational projects happen with creativity and motivation. Meanwhile, social entrepreneurship in less favored contexts appears as a promising route for renewing social intervention, being an alternative form of economic production. The growth in the number of studies on entrepreneurship in recent decades has increased the visibility and importance of the topic, however the topic of entrepreneurial education still needs a more solid discussion, which would help in its maturation, guidance and dissemination more effectively. Therefore, this quali-quanti study focuses on the topic of entrepreneurial education, with the objective of enabling the entrepreneurial training of young people in contexts of socioeconomic vulnerability. To this end, the topic “entrepreneurship” and methodologies for teaching it were researched. The Business CANVAS methodology was chosen for the application of research in the field, as it is more practical, simple and easily accessible. In the field, research was carried out with a sample of 47 young people in contexts of socioeconomic vulnerability. Finally, for data analysis, a descriptive analysis of all CANVAS applied during the research process was used. With this analysis, the research results showed that teaching entrepreneurship to young people in vulnerable contexts goes far beyond pragmatic and theoretical content, it means changing a generation, promoting proactivity, dream fulfillment, reflection, responsibility, self-knowledge, self-valuation, to permeate entrepreneurial skills, attitudes and behaviors. Therefore, it is concluded that it is necessary to develop approaches, techniques and tools for teaching entrepreneurship, which consider the context and promote, in addition to the productive inclusion of young people, social inclusion and personal development for the protagonism of young people in socioeconomic vulnerability.